BOARD ATTRIBUTES AND TIMELINESS OF FINANCIAL REPORTS OF LISTED NON-FINANCIAL FIRMS IN NIGERIA - Rashida Lawal; Kabir Hamid Tahir (Gusau Journal of Accounting and Finance)
This study is on board attributes and timeliness of financial reports of listed non-financial firms in Nigeria. The study covers a period of ten (10) years from 2011 to 2020. The study embraced the correlational research design. The population of the study comprises of one hundred and fourteen (114) non-financial firms that are listed on the NXG as at 31st December 2020 out of which sixty (60) was selected using a two-point filter to eliminate the firms that has not fulfil the criteria for the sample selection for the study. The dependent variable of the study is timeliness of financial reports and is proxied by audit report lag. The independent variable which is board attributes is proxied by board size and board gender. While the control variable profitability and firm size. Board attribute was found to have a negative and significant impact on timeliness of financial report of listed non-financial firms in Nigeria. This implies that for every increase in the board size and an increase in the number of females on the board, there is a significant reduction in the audit report lag among listed non-financial firms in Nigeria. It can be concluded that board attribute reduces audit report delay among listed non-financial firms in Nigeria. It is therefore recommended that the board of directors of listed non-financial firms should reduce the level of leverage in their capital structure since it was found that delay in audit report increases with an increase in leverage.